Interspecific Sample Prioritization Can Improve QTL Detection With Tree-Based Predictive Models - Shin, Min-Gyoung; Nuzhdin, Sergey V. (Frontiers in Genetics, 2021)
Due to increasing demand for new advanced crops, considerable efforts have been made to explore the improvement of stress and disease resistance cultivar traits through the study of wild crops. When both wild and interspecific hybrid materials are available, a common approach has been to study two types of materials separately and simply compare the QTL regions. However, combining the two types of materials can potentially create a more efficient method of finding predictive QTLs. In this simulation study we focused on scenarios involving causal marker expression suppressed by trans-regulatory mechanisms, where the otherwise easily lost associated signals benefit the most from combining the two types of data. A probabilistic sampling approach was used to prioritize consistent genotypic phenotypic patterns across both types of data sets. We chose Random Forest and Gradient Boosting to apply the prioritization scheme and found that it facilitated investigation of predictive causal markers in most of the biological scenarios simulated.